2021
DOI: 10.1186/s40337-021-00469-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of group cognitive behavior therapy on Chinese patients with anorexia nervosa: an open label trial

Abstract: Background The high cost of treatment for anorexia nervosa (AN) and lack of trained specialists have resulted in limited accessibility of effective treatment to patients with AN, which is particularly problematic in China. To increase the accessibility of evidence-based treatment and reduce the cost of treatment, this study aimed to explore the feasibility and efficacy of group cognitive behavior therapy (G-CBT) adapted from enhanced cognitive behavior therapy for eating disorders (CBT-E) in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…GCBT showed significant improvement in eating pathology and associated psychopathology throughout treatment. [12] Moreover, Lin et al investigated the effectiveness of GCBT on depression and suicide reattempt and emotion regulation strategies among those with borderline personality disorder. They showed that GCBT effectively decreased depression and suicide reattempt in Borderline Personality Disorder college students, probably through increasing adaptive antecedent-focused or response-focused strategies of emotion regulation, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCBT showed significant improvement in eating pathology and associated psychopathology throughout treatment. [12] Moreover, Lin et al investigated the effectiveness of GCBT on depression and suicide reattempt and emotion regulation strategies among those with borderline personality disorder. They showed that GCBT effectively decreased depression and suicide reattempt in Borderline Personality Disorder college students, probably through increasing adaptive antecedent-focused or response-focused strategies of emotion regulation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies included crimination among HIV-positive Latino sexual minority men [7] ; individuals with anxiety, depression, and suicide reattempts [8,9] ; women diagnosed with bipolar disorder; major depressive disorder spectrum seeking help for menopausal symptoms [10] ; women with AD [11] ; and Chinese patients with anorexia nervosa. [12] The present study was designed to investigate the efficacy of GCBT in male Chinese patients with AD to provide an effective approach for patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of local diet and eating behaviors (Gu et al, 2021;Hamatani et al, 2022, b) Addition of Chinese traditional music for relaxation (Wang & Xiao, 2021) Value/importance of family/community Incorporation of the concept of extended family in the assessment and treatment (Ma & Lai, 2009) Language translation Addition of Korean subtitles (Kim et al, 2019), translation of manual to Japanese (Hamatani et al, 2022, b) Language tailoring Use of a less direct communication style when recommending behavioral changes in Japan (Hamatani et al, 2022, b) Provision of explanations of psychological terms such as rumination was changed to rumination (negatively, dwell on; Hamatani et al, 2022, b) Methodological components…”
Section: Illustrated Traditionsmentioning
confidence: 99%
“…This is due to the lack of specialist treatment centres and trained personnel, yet the demand was high (Okamoto et al, 2017); It was less costly to patients given the healthcare system was not free (Gu et al, 2021;Okamoto et al, 2017); Group treatments can help build confidence and for Japanese individuals to feel less guilty about having an ED (Okamoto et al, 2017) Use of lower intensity treatments (e.g., guided self-help) to increase access due to the lack of specialized services in the community (Setsu et al, 2018); Shortening of treatment to 10 sessions (e.g., Shiina et al, 2005) to make treatment more affordable and acceptable, as some people lived far away (Gu et al, 2021) Theoretical framework Use of the Formative Method for Adapting Psychotherapy (FMAP) when culturally adapting treatment (Hamatani et al, 2022, b) lack of specialist treatment centres, so that trained clinicians could see more patients (Okamoto et al, 2017). Another reason for shortening treatments, was to make them more affordable, as most healthcare systems described were not free and people lived far away from any specialist centres (Gu et al, 2021). Some treatments were conducted in general medicine (AN intervention, Amemiya et al, 2012) or pediatric settings (ARFID interventions, Tamura et al, 2021;Tomioka et al, 2022) rather than in specialist ED units.…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation